2004
DOI: 10.1016/j.jelechem.2003.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrovoltaic cells. Part II: Thermogalvanic cells and numerical simulations of thermal diffusion potentials

Abstract: When two electrolyte solutions of different temperature are placed in contact, a thermal diffusion potential (TDP) is established. The phenomenon is studied numerically using finite element simulations of the temperature distribution within a hydrodynamic cell. Experimentally, the hydrovoltaic flow cell is used to demonstrate how a temperature difference can induce redox reactions at electrodes placed in the two liquids in order to extract a current continuously in an external circuit resulting in a power-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In a series of papers, Girault's group demonstrated (Josserand et al , 2004Lagger et al 2003) how the diffusion potential between two laminar flows of electrolyte solutions can be used as the basis of a hydro-voltaic cell. Munson et al (2002) showed that the diffusion potential established in a microchannel can induce appreciable electrophoretic transport of charged species without the use of external power.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of papers, Girault's group demonstrated (Josserand et al , 2004Lagger et al 2003) how the diffusion potential between two laminar flows of electrolyte solutions can be used as the basis of a hydro-voltaic cell. Munson et al (2002) showed that the diffusion potential established in a microchannel can induce appreciable electrophoretic transport of charged species without the use of external power.…”
Section: Introductionmentioning
confidence: 99%
“…The ferri/ferrocyanide redox couple, where n = 1, is known to produce a relatively high reaction entropy, so we here focus on increasing the parameters that critically limit thermocell efficiency, j SC and R T . The intrinsically large surface area of MWNTs and fast electron transfer between MWNT electrodes and electrolyte directly enhance j SC . Thermal conduction losses are mitigated (i.e., R T is increased) using two primary approaches that also enhance j SC , (1) we took advantage of the highly porous three-dimensional structure of MWNT buckypaper by using scroll-like electrodes, which are commonly used in batteries and capacitors, to reduce cross-sectional area normal to the direction of heat flow while allowing a high degree of electrolyte exposure to the electrode surface for redox reactions to occur, and (2) we directly synthesized vertically aligned MWNT arrays (i.e., nanotube forests) to establish electrodes that are in good thermal and electrical contact with the thermocell packaging. , …”
mentioning
confidence: 99%
“…[ 1 ] Different technologies for converting low‐grade heat into electricity, such as solid‐state thermoelectric energy conversion and organic Rankine cycles, are being widely investigated but face challenges in low power densities, high material and/or operational costs, lack of capacities for energy storage, system complexity, and low heat‐to‐electricity conversion efficiencies, etc., which hinder their deployment. [ 2 ] Thermogalvanic cells including thermogalvanic flow cell [ 3 ] and hydrovoltaic cell, [ 4 ] offer an alternative and inexpensive route for direct thermal‐to‐electric energy conversion without producing emissions or consuming any materials. However, the low conductivity factor (i.e., the ratio of electrical and thermal conductivity) of the electrolytes leads to poor thermoelectric performance.…”
Section: Figurementioning
confidence: 99%